Respon Masyarakat Surabaya terhadap Diputuskannya RUU Cipta Kerja Oleh Pemerintah - Taufiqurahman Arsy Ramadhani; Agus Machfud Fauzi (Universitas Batanghari Jambi, 2020)
This article aims to analyze the response of the Indonesian people after the decision on the Job Creation Bill drafted by the DPR. The method used in this research is descriptive qualitative research method by explaining the sociological view of law on the impact resulting from the decision of the Work Creation Bill to become a permanent law. The data collection technique used is to collect literature studies, namely taking from several sources such as journals, articles , news, magazines or other sources related to the topic being discussed. The results of this study are expected to be a reference for future studies and can provide useful knowledge for readers.